Papillary Thyroid Carcinoma Presented with Huge Bone Metastases Right Ileum and Frontal Bones (Bangladesh Journal of Nuclear Medicine, 2015)
Papillary thyroid carcinoma (PTC) without metastases is most curable cancer. However, it rarely metastasizes to bone and in those cases prognosis is poor. A 55 years old female has presented with history of painless swelling on frontal region of skull for one year and limping gait to National Institute of Nuclear Medicine and Allied Sciences (NINMAS) in September 2013. She also had total thyroidectomy for multinodular goiter in early 2013. She had history of excision of swelling on frontal region in July of same year. Histopathological report of excised mass confirmed metastatic PTC. The patient again developed visible swelling on frontal region of skull suggesting recurrence. Her serum TSH was low 0.89 mIU/L without levothyroxine supplement may be due to thyroid hormones produced from metastatic masses. Serum thyroglobulin level was 464 ng/ml. X-ray of pelvis and skull showed huge soft tissue masses arising from right ileum and a lytic lesion on posterior aspect of frontal region. Whole body bone scan with 99m Technetium methylene diphosphonate (MDP) revealed a doughnut lesion of frontal bone and a big lesion with hot and cold areas in right ileum and. On ultrasound scan, there was huge solid mass (about 10.0 cm× 7.0 cm) with some inhomogeneity and central cystic changes in medial aspect of right hip bone extending to pelvic cavity. Similar mass corresponded the visible swelling on skull. This mass was extended to intracranial region. Color Doppler study showed vascularity within and at margins of masses. To avoid risk of raised intracranial pressure following radioiodine therapy we sent the patient for external beam radiation therapy (EBRT) for reduction of the size of masses. Patient under went 5 cycles of EBRT (total 2000 c Gy in each lesion) but there were no reductions of sizes within one month follow up period. Small bony metastatic lesions from PTC in early stage are curable by surgical removal and repeated dose of radioiodine therapy. PTC with multiple advanced bony metastases shows poor prognosis. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22504 Bangladesh J. Nuclear Med. 17(1): 125-132, January 2014